Test the Number of Stirring Bar in Grated Coconut Dryers - Friani Parsaulian; Lukman Adlin Harahap; Achwil Putra Munir (Jurnal Rekayasa Pangan dan Pertanian, 2016)
Coconut plant is a plant of life, because all its parts can be utilized to meet human needs. One of the utilization is grated coconut that can to be used in making bread, biscuits, sweets, its milk and coconut flour. This study was aimed to examine the effect of the number of rod in manufacturing of desiccated coconut on the performance of the grated coconut dryer. This research was conducted in March and May 2015 in the Laboratory of Agricultural Engineering, Faculty of Agriculture, University of North Sumatra, Medan, by literature study, testing equipment and parameters observation. Parameters measured were moisture content, percentage of materials left in the appliance, yield and organoleptic tests. The results showed that the number of rod was not significantly affected the water content, yield and organoleptic tests and significantly affected to the percentage of material left in the appliance. Key words: desiccated coconut, grated coconut dryer, stirring bar.